2022
DOI: 10.31234/osf.io/4gyzh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does alleviating poverty increase cognitive performance? Short and long term evidence from a randomized controlled trial

Abstract: In this Registered Report, we investigated the impact of a poverty alleviation program on cognitive performance. We analyzed data from a randomized controlled trial conducted on low-income, high-risk individuals in Liberia where a random half of the participants (n=251) received a $200 lump-sum unconditional cash transfer - equivalent approximately to 300% of their monthly income - while the other half (n= 222) did not.We tested both the short-term (2-5 weeks) and the long-term (12-13 months) impact of the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Notably, the effects found in this study were roughly four times smaller than effect sizes observed in prior non-experimental research. Given the observed effect size, we would have needed a sample of 4750 participants to find strong Bayesian evidence 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the effects found in this study were roughly four times smaller than effect sizes observed in prior non-experimental research. Given the observed effect size, we would have needed a sample of 4750 participants to find strong Bayesian evidence 6 .…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies show that living in financial scarcity has a negative impact on cognitive functioning [1][2][3][4][5][6] and that decreased cognitive functioning limits the economic opportunities of the poor [7][8][9] . If so, impaired cognitive performance is one important pathway through which the self-reinforcing cycles of poverty are perpetuated 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Although scarcity theory has no specific prediction about which subcomponent of cognitive functions is more impacted by financial scarcity, some prior research suggest that some subcomponents could be affected more than others (Szaszi et al, 2022). The identified studies mainly investigated cognitive control and fluid intelligence, missing important components of cognitive functioning (e.g., memory, attention).…”
Section: Focus On Different Facets Of Cognitive Functioningmentioning
confidence: 99%
“…These results have to be treated with a number of limitations in mind. First, no computational distinction was made between different cognitive performance outcome variables, although prior research on the topic of relationship between poverty and cognitive performance suggests that the use of different measures can lead to different results (Szaszi et al, 2022). Second, there are studies that contain suggestive evidence regarding the effect (Destin & Svoboda, 2018;Duquennois, 2022) but were not included in the meta-analysis due to not meeting our inclusion criteria such as providing causal evidence or having individuallevel outcome data.…”
Section: Limitationsmentioning
confidence: 99%